PERISTILAHAN DALAM UPACARA ADAT ABUH DAPOR LAWAKNG TANGAK DAYAK SIMPAKNG - Mina, Brigita; Salem, Laurensius; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe research problem of this study is, how is the terminology in abuh dapor lawakng tangak traditional ceremony. The general problem is limited to four subproblems: description of terminology description, component of meaning, and lexical meaning. The method used in this research is conversation and descriptive method using qualitative form. Techniques used were interview and live conversations. Data collection tools used were a research instrument in the form of sentences (to filter the data asked by the researcher to the informant), data card used to facilitate data and recorder. Based on data analysis that has been done by researcher, can be concluded that from the five categories of the abuh, the researcher succeeded in collecting 33 terminology in the process of performing the abuh dapor lawakng tangak traditional ceremony covering the five categories of abuh, 20 terms of custom rite equipment in traditional ceremony of abuh kahagokng and abuh agokng, 19 terminology of custom rite equipment in traditional ceremony of abuh bagi, abuh popah, dan abuh naribokng, 33 terminology of banquet equipment, 17 terminology of foodstuff, and 12Â terminology of food names.Â Keywords: Abuh dapor, lawakng tangak, lexical meaning.